Stability of the Simplest Periodic Solutions in the Stuart–Landau Equation with Large Delay - A. A. Kashchenko (Моделирование и анализ информационных систем)
We study the local dynamics of the Stuart–Landau equation with large delay in the neibourhood of periodic solutions. We find sufficient conditions of instability of periodic solutions and sufficient conditions of their stability.